Financial Protection of Patients through Compensation of Providers: The Impact of Health Equity Funds in Cambodia - Gabriela Flores; Por Ir; Chean R. Men; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2011)
Public providers have no financial incentive to respect their legal obligation to exempt the poor from user fees. Health Equity Funds (HEFs) aim to make exemptions effective by giving NGOs responsibility for assessing eligibility and compensating providers for lost revenue. We use the geographic spread of HEFs in Cambodia to identify their impact on out-of-pocket (OOP) payments. Among households with some OOP payment, HEFs reduce the amount by 29%, on average. The effect is larger for households that are poorer, mainly use public health care and live closer to a district hospital. HEFs are more effective in reducing OOP payments when they are operated by a NGO, rather than the government, and when they operate in conjunction with the contracting of public health services. HEFs reduce households' health-related debt by around 25%, on average. There is no significant impact on non-medical consumption and health care utilisation.
urn:NBN:nl:ui:15-1765/30602
Keywords: H42; H51; I18; 330; Health Financing; User Fees; Financial Protection; Health Care; Cambodia